A clinico-pathological study of pigmented cutaneous lesions: a one-year prospective study in a tertiary care hospital - Parvathi, M.; Balaji, Chowdari; Lekha, G. Divya; Kumar, S. Satish; Lakshmi, A. Bhagya (International Journal of Research in Medical Sciences, 2017)
Background: Pigmented lesions are group of lesions which have melanocytic proliferation with very common clinical presentation. Diagnosing these pigmented lesions and differentiating cutaneous melanocytic lesions from non-melanocytic lesions poses a great challenge for the pathologist. Methods: A Prospective study was conducted for one year from June 2016 to June 2017 sent to the Department of Pathology, Andhra Medical College, Visakhapatnam, a tertiary care centre in southern India consisting of 44 pigmented lesions. Specimens were formalin fixed and the tissue was adequately processed for histopathological examination. The sections were stained routinely with hematoxylin and eosin stain and examined under light microscopy. Results: Out of 44 cases, 24 cases were cutaneous melanocytic lesions which include benign naevi 22 (50%) and 2 (4.6%) malignant melanoma cases. The other 20 cases were cutaneous non melanocytic lesions which include 5 (11.4%) pigmented seborrheic keratosis, 6 (13.7%) pigmented basal cell carcinoma, 1 (2.3%) pigmented actinic keratosis and 8 (18%) cases of naevus sebaceous. Most common effected age group was <21 years (31.81%), male: female ratio is 1:2 and most common site involved was face 29 cases (65.9%). Most common pigmented lesions were benign melanocytic nevi 22 (50%) followed by naevus sebaceous 8 (18%) cases. 32 (72.71%) cases were consistent with both clinico-histopathological correlation. Conclusions: Benign melanocytic nevi are most common lesions obtained, seborric keratosis and pigmented basal cell carcinoma were most common mimickers of melanocytic lesions, hence a careful histopathological diagnosis is important.